2015
DOI: 10.1007/s00270-015-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraprocedural 3D Quantification of Lipiodol Deposition on Cone-Beam CT Predicts Tumor Response After Transarterial Chemoembolization in Patients with Hepatocellular Carcinoma

Abstract: Purpose To evaluate whether intraprocedural 3D quantification of Lipiodol deposition on cone-beam computed tomography (CBCT) can predict tumor response on follow-up contrast-enhanced magnetic resonance imaging (CE-MRI) in patients with hepatocellular carcinoma (HCC) treated with conventional transarterial chemoembolization (cTACE). Materials and Methods This IRB approved, retrospective analysis included 36 patients with 51 HCC target lesions, who underwent cTACE with CBCT. CE-MRI was acquired at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…A preliminary study showed a strong correlation between the virtual perfusion territories on non-selective CBCTHA and the actual selective injection areas on selective CBCTHA with an average dice of 0.76, an average surface-to-surface distance of 4.4 mm, and an average volume error of 14%. 19 In the present study, the dimensions and volume of the VEA and REA correlated well in the majority of tumors. In our study protocol, however, all CBCT images were obtained in the expiratory phase, and CT images were obtained in the inspiratory phase.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A preliminary study showed a strong correlation between the virtual perfusion territories on non-selective CBCTHA and the actual selective injection areas on selective CBCTHA with an average dice of 0.76, an average surface-to-surface distance of 4.4 mm, and an average volume error of 14%. 19 In the present study, the dimensions and volume of the VEA and REA correlated well in the majority of tumors. In our study protocol, however, all CBCT images were obtained in the expiratory phase, and CT images were obtained in the inspiratory phase.…”
Section: Discussionsupporting
confidence: 67%
“…The extraction of any vascular territory can be carried out instantly on the workstation. A preliminary study showed a strong correlation between the virtual perfusion territories on non‐selective CBCTHA and the actual selective injection areas on selective CBCTHA with an average dice of 0.76, an average surface‐to‐surface distance of 4.4 mm, and an average volume error of 14% …”
Section: Discussionmentioning
confidence: 99%
“…This is the first study comparing these two couples of CBCT data achieved during RE with HCC patients. Previous studies done with TACE easily pointed out the post-embolisation effect as an expected outcome of the embolic nature of TACE [15,16]. There is only one RE study on DP-CBCT using quantitative measurement methods, which involved a liver metastasis patient group using arbitrary units (AU), in the English language literature [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CBCT usage has been correlated with better procedural outcome: Wang et al (32) demonstrated a strong correlation between lipiodol deposition on CBCT and tumor necrosis (cm 3 ) assessed with enhanced MRI.…”
Section: Intraprocedural Implicationsmentioning
confidence: 99%